Being known [large type] - Gunn, Robin Jones, 1955- (Haven makers, 2020)
"After her mom passed away, Jennalyn was in the midst of moving, adjusting to life with a new baby, and helping her husband, Joel, work toward his dream job. At the time, she thought she'd processed her mother's death, but only now that Jennalyn has two small children, a lovely new home, and a husband who is always working does she feel the full impact of what she has lost. Even among her sweet circle of friends, the Haven Makers, grief silently overwhelms Jennalyn, until an unexpected encounter allows her to express herself in ways she hasn't fully been able to with her husband. Even though Christy, Sierra, Emily, and Tess provide a soft place to land in times of tension, Jennalyn remains guarded, especially when Tess reveals she is tangled emotionally in a relationship that was thorny from the start. Will the two women open up and remain honest with the others in their Haven Makers group? Or will their hesitation to truly be known, faults and all, keep them from holding on to the friendships that have been the sweetest gift during this season of life?"--